Influence of Abiotic Factors on Population Dynamics of Sucking Insect Pests and their Natural Enemies in Brinjal - Saini, Laxman Singh (Annals of Arid Zone, 2025)
The study investigated the population dynamics of whitefly, leaf hopper, lady bird beetle and spider in kharif, 2022 and 2023, revealing distinct patterns and correlations with weather parameters. Whitefly infestations started in last week of August with initial populations of 6.6 and 7.84 per 3 leaves, peaked at 31.08 and 34.76 per 3 leaves in early October. Leaf hopper populations started in last week of August with 5.24 and 5.96 per 3 leaves, peaked at 25.48 and 28.12 per 3 leaves in last week of September and early October. Lady bird beetles appeared in early September with initial populations of 0.88 and 1.20 per 5 plant, peaked at 3.96 and 4.24 per 5 plant in mid-October. Spider populations started in early September with 1.12 and 0.96 per 5 plant, peaked at 3.04 and 3.44 per 5 plant in second fortnight of October. Correlation analysis showed significant positive correlations between whitefly and maximum temperature (r = 0.66 and 0.61), with significant negative correlations with morning relative humidity in 2022 (r = -0.52). Leaf hopper populations had significant positive correlations with maximum temperature (r = 0.69 and 0.68) and minimum temperature in 2022 (r = 0.64). Lady bird beetles had significant positive correlations with maximum temperature (r = 0.50 and 0.52), while spiders also showed significant positive correlations with maximum temperature (r = 0.50 and 0.50). Multiple linear regression analysis explained a significant portion of population variation due to abiotic factors: 65% and 74% for whiteflies; 61% and 70% for leaf hoppers; 77% and 71% for lady bird beetles and 75% and 72% for spiders in kharif, 2022 and 2023, respectively.